Submucosal metastatic leiomyosarcoma of the colon presenting with intussusception and lower gastrointestinal bleeding: a case report - Li, Honghai; Yu, Zunfang; Ye, Minfeng; Jin, Qijing (Frontiers in Oncology, 2026)
Colonic leiomyosarcoma (LMS) is a highly aggressive tumor arising from smooth muscle cells and is generally associated with a poor prognosis. This report presents a case of colonic LMS originating from the submucosal layer of the ascending colon. A 76-year-old woman was admitted with intermittent hematochezia persisting for over a month. Imaging studies revealed a tumor in the ascending colon accompanied by intussusception. The patient underwent a right hemicolectomy with systematic lymphadenectomy involving the middle colic root and right branch regions. Postoperative histopathological analysis confirmed colonic LMS arising from the submucosa, with no evidence of lymph node metastasis. Colonic intussusception secondary to LMS is extremely rare, and, to our knowledge, no previous cases of colonic intussusception caused by metastatic sarcoma have been reported. It remains uncertain whether the tumor originated primarily in the colon or resulted from hematogenous metastasis to the colonic mucosa.